2017
DOI: 10.1021/acsenergylett.7b00865
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intercalated Metals on the Electrocatalytic Activity of 1T-MoS2 for the Hydrogen Evolution Reaction

Abstract: We show that intercalation of cations (Na+, Ca2+, Ni2+, and Co2+) into the interlayer region of 1T-MoS2 is an effective strategy to lower the overpotential for the hydrogen evolution reaction (HER). In acidic media the onset potential for 1T-MoS2 with intercalated ions is lowered by ∼60 mV relative to that for pristine 1T-MoS2 (onset of ∼180 mV). Density functional theory (DFT) calculations show a lowering in the Gibbs free energy for H-adsorption (ΔG H) on these intercalated structures relative to intercalant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
188
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(198 citation statements)
references
References 45 publications
10
188
0
Order By: Relevance
“…These results strongly illustrate that CNTs join the composite to enhance the electrocatalytic activity, which was further confirmed by the small Tafel slope of 77 mV dec −1 of the PDMS−CNTs@MnO 2 sponge, because of the joint effect of CNTs and MnO 2 on enhancing electrocatalytic activity. The PDMS−CNTs sponge@MnO 2 showed the smallest Tafel slope of 71 mV dec −1 , approximate close to Pt/C in the reported values in the literature . As shown in Figure c, the combination of CNTs and MnO 2 resulted in an efficient functional electrocatalyst of PDMS−CNTs sponge@MnO 2 for HER.…”
Section: Resultssupporting
confidence: 83%
“…These results strongly illustrate that CNTs join the composite to enhance the electrocatalytic activity, which was further confirmed by the small Tafel slope of 77 mV dec −1 of the PDMS−CNTs@MnO 2 sponge, because of the joint effect of CNTs and MnO 2 on enhancing electrocatalytic activity. The PDMS−CNTs sponge@MnO 2 showed the smallest Tafel slope of 71 mV dec −1 , approximate close to Pt/C in the reported values in the literature . As shown in Figure c, the combination of CNTs and MnO 2 resulted in an efficient functional electrocatalyst of PDMS−CNTs sponge@MnO 2 for HER.…”
Section: Resultssupporting
confidence: 83%
“…The HER performance is comparable with recently reported MoS 2 -based electrocatalysts. [20,22,24,27,38,32] It may be due to the improved in-plane electrical conductivity and carrier concentration of MoS 2 after nitrogen doping as observed in earlier cases for the nitrogen-manganese co-doped MoS 2 and nick-el@N-doped carbon@MoS 2 systems. [38,40] Therefore, the HER activity enhancement can be related to the N dopants in the MoS 2 crystal structure.…”
Section: Resultsmentioning
confidence: 65%
“…The other two relatively weak characteristic peaks appeared at ∼284 and 450 cm −1 belong to the E 1g and longitudinal acoustic phonon mode (2 nd order Raman scattering) for both 2H phase and hybrid phase composition. The spectrum drawn by a black color line contained three new characteristic peaks at 151, 234 and 340 cm −1 correspond to distinct phonon modes of J 1 , J 2 and J 3 , respectively, evidently signifying the formation of 1T@2H hybrid phase . The Raman spectra (Figure S1) of different phases of NMS1 and NMS3 agreed well with the XRD patterns shown in Figure (a‐c).…”
Section: Resultsmentioning
confidence: 98%
“…Nuvan et al. have also demonstrated that the higher interlayer spacing in 1T‐MoS 2 caused by the intercalation of metal cations showed reduced the overpotentials . Vertically aligned MoS 2 nanoflakes on the CC are very efficient in providing more active edge sites for the proton adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Nuvan et al have also demonstrated that the higher interlayer spacing in 1T-MoS 2 caused by the intercalation of metal cations showed reduced the overpotentials. [48] Vertically aligned MoS 2 nanoflakes on the CC are very efficient in providing more active edge sites for the proton adsorption. Furthermore, the direct growth of the MoS 2 onto the CC could reduce the contact resistance between the MoS 2 flakes and the current collector (carbon cloth).…”
Section: Electrocatalytic Hermentioning
confidence: 99%